The Relationship Between Knowledge About Antenatal Care And The Regularity Of Anc Visits At Pmb Dutha Muara Kelingi Sub-District Year 2024 - Juliana, Nova; Annisa, Kintan; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2024)
Based on the Indonesian Ministry of Health (2020), it is stated that, ‘Services that must be provided during pregnancy include ANC at least 6 visits, which are detailed twice in Trimester I, once in Trimester II, and 3 times in Trimester III. At least 2 examinations are carried out by a doctor during the 1st visit in Trimester I and during the 5th visit in Trimester 3. The purpose of this study was to determine the relationship between knowledge about antenatal care and regularity of pregnancy examination visits at PMB Dutha Muara Kelingi District. The method used is analytical research design with a Cross Sectional approach, data collected by distributing questionnaires to 105 respondents using total random sampling technique. The results of the univariate test analysis that almost half of the respondents who were less knowledgeable were (69.5%), and irregular visits were (69.5%). The results of bivariate analysis there is a significant relationship between maternal knowledge about antenatal care (ANC) with the regularity of antenatal care visits (ANC) for pregnant women at PMB Dutha Muara Kelingi, where the p-value is 0.030 <0.05. The results of this study will add to the reference, and prove whether or not there is a relationship between maternal knowledge about antenatal care (ANC) with the regularity of antenatal care visits (ANC) for pregnant women at PMB Dutha Muara Kelingi.